UMKM Citra Niaga di Samarinda - Siti Maria; Said Saleh Fathurahman; Cintya Feby Pratiwi; Ferdhy Adhitya Putra; Fathur Rahman; Ricco Yunanto; Sukma Nandha Krisnyongningtyas (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
UMKM sector during the Covid-19 pandemic has had various problems. Such as, decreased sales, capital, hampered distribution, difficulties with raw materials. UMKM players have also changed their marketing orientation due to the pandemic, many UMKM players have switched to online trading to increase sales but this is not supported by the ability of UMKM players who tend to be low in using technology. This service aims to provide understanding and skills for UMKM in KHADIJAH SOUVENIR Samarinda regarding the use of social media as an effective and efficient means of product sales/promotion as a means of selling products. This activity uses a contextual approach method, namely providing theoretical material first and directly uploading products produced by KHADIJAH SOUVENIR UMKM actors. The result of this activity is the partners' understanding of marketing via social media; able to create promotions via social media independently.